Experiences of early adopters in changing their thinking regarding teaching practices for the online environment in a New Zealand university : a thesis presented in partial fulfilment of the requirements of the degree of Master of Education in Adult Education at Massey University - Hallas, Julia Leah (Massey University, 2005)
The aim of this thesis was to investigate how early adopters changed their thinking regarding teaching practices for the online environment. The study investigated how early adopters adapted and developed their classroom based teaching practices for the online environment, the effect of online teaching practices on their students' learning, and the types of professional development lecturers engaged in to learn about online teaching practices. A mainly qualitative approach, within a case study method, was used to undertake the research in a medium sized, New Zealand university, where the researcher is an academic developer in the centralised professional development unit, jointly responsible for supporting staff in online teaching practices. Written informed consent was obtained from lecturers participating in this study. A mail-in survey, individual interviews and online course observations were used to gather data for the research questions. This is a limited case study owing to the small size of the sample. The study concluded that early adopters changed their thinking about teaching practices over time, adapting and developing student-centred approaches to learning for the online environment. The study found that early adopters' perceptions of student learning was of a higher quality online, than in the classroom, owing to student learning approaches being deeper, more interactive and collaborative. Finally, the study showed that a majority of early adopters did not engage in research based professional development activities, which made changing their thinking from teacher-centred to student-centred online teaching practices, difficult and stressful.
Keywords: New Zealand; Computer network resources; Internet in higher education; Education, Higher; College teaching